2022
DOI: 10.5194/bg-19-3021-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change in European croplands and grasslands: productivity, greenhouse gas balance and soil carbon storage

Abstract: Abstract. Knowledge of the effects of climate change on agro-ecosystems is fundamental to identifying local actions aimed to maintain productivity and reduce environmental issues. This study investigates the effects of climate perturbation on the European crop and grassland production systems, combining the findings from two specific biogeochemical models. Accurate and high-resolution management and pedoclimatic data were employed. Results have been verified for the period 1978–2004 (historical period) and pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 141 publications
5
5
0
Order By: Relevance
“…Our findings are in agreement with those of recent research on climate change impacts on crops in southern Europe and north-eastern Mediterranean, regarding wheat [90][91][92][93][94], barley [91], maize [90,92], rice [95], vegetables [10,91,96], potatoes [97], olives [91,[98][99][100], vines [91,96,101,102], legumes [103], alfalfa [104,105], sunflower [106], fruit trees [107,108] and nut trees [109][110][111].…”
Section: Effect Of Long-term Climate Change On Crop Yields In Greecesupporting
confidence: 93%
“…Our findings are in agreement with those of recent research on climate change impacts on crops in southern Europe and north-eastern Mediterranean, regarding wheat [90][91][92][93][94], barley [91], maize [90,92], rice [95], vegetables [10,91,96], potatoes [97], olives [91,[98][99][100], vines [91,96,101,102], legumes [103], alfalfa [104,105], sunflower [106], fruit trees [107,108] and nut trees [109][110][111].…”
Section: Effect Of Long-term Climate Change On Crop Yields In Greecesupporting
confidence: 93%
“…Climate change associated changes in temperature and precipitation induce an increase in net GHG emissions, caused by SOC storage loss and CH 4 manure emissions increase (Table 2). This result is similar to Carozzi et al (2022) for European grasslands under similar climate change scenarios. Carozzi et al (2022) showed that on-CO 2 GHG emissions were triggered by rising air temperatures and increased exponentially over the century while exceeding the CO 2 accumulation.…”
Section: Net Ghg Emissionssupporting
confidence: 85%
“…This result is similar to Carozzi et al (2022) for European grasslands under similar climate change scenarios. Carozzi et al (2022) showed that on-CO 2 GHG emissions were triggered by rising air temperatures and increased exponentially over the century while exceeding the CO 2 accumulation. Graux et al (2012), evaluating French grasslandbased dairy systems under the IPCC special report emissions scenario (SRES) A2 forcing conditions, showed an increase in net GHG emissions in extensively managed grassland systems and a reduction in net GHG in intensively managed grassland systems (where SOM decomposition acceleration is compensated for by enhanced net primary production).…”
Section: Net Ghg Emissionssupporting
confidence: 85%
“…However, this phenomenon allows northern European countries to enhance crop conditions [6,31]. A study by Carozzi et al [32] predicts a significant reduction in cereal productivity between 2050 and 2099 due to a reduction in the length of the crop-growing cycle associated with rising temperatures. This effect was more pronounced for the more pessimistic climate scenario (-13% for croplands and -7.7% for grasslands) and Mediterranean regions, confirming a regionally distributed impact of climate change.…”
mentioning
confidence: 99%
“…The interconnections between environmental deterioration caused by CO₂ emissions and economic factors represent a significant area of research within the broader field of environmental Kuznets curve (EKC) studies. The EKC hypothesis posits the existence of nonlinear relationships between socio-economic development and environmental CO₂ pollution [32][33][34]. In most studies, it has been observed that CO₂ emissions initially increase with economic growth but eventually decrease with increasing income levels of society.…”
mentioning
confidence: 99%